Hyperpigmented nevus. - Bonifazi, E.; Milano, A.; Caprio, F.; Garofalo, L. (European Journal of Pediatric Dermatology, 2011)
Hyperpigmented nevus is a common skin lesion characterized by an increased content of melanin in the epidermis with a normal number of melanocytes, but in literature there are only a few very large cases. This paper describes the characteristics of 489 clinical cases of hyperpigmented nevus and focuses on its differential diagnosis, particularly from segmental neurofibromatosis.